Debates on Social Exclusion and Inclusion in Nepal - Ghimire, Dipesh (KMC Research Journal, 2018)
The term “Social Exclusion” is used to describe a wide range of phenomena and processes related not only to poverty and deprivation, but also to social, cultural and political disadvantages, and in relation to a wide range of categories of excluded people. However, there is no single way of understanding the concepts of social exclusion and inclusion. In the context of Nepal, power was consolidated by interlinking it with the Hindu caste system. The social order was exclusionary because it classified all groups as distinct castes within the broad framework of the Hindu system of the four varnas based on concepts of ritual purity and pollution. This paper has attempted to present a quick and preliminary discussion on theoretical perspectives on social exclusion and inclusion. The paper has also emphasized on the major debates on social exclusion and inclusion in Nepal and thematic aspects of social exclusion and inclusion.